Peran Kepercayaan Pasien Memediasi Pengaruh Citra dan Keterlibatan Pasien terhadap Kepuasan Pasien di Klinik Mata Tritya Surabaya - A Triartomo; Siti Mujanah; Achmad Yanu Alif Fianto (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The main goal of health agencies is patient satisfaction. Patient satisfaction is formed from the success of health agencies in curing patient illnesses. This study investigates the influence of image and patient involvement on patient trust. Also investigate whether patient beliefs are a good mediator. This study conducted a survey of patients at the Tritya Surabaya eye clinic. Using a purposive sampling method, and a research sample of 70 respondents, the data was then analyzed using Structural Equation Modeling. The findings show that image and patient engagement make a positive contribution to patient trust. Research also proves that patient trust mediates the relationship between patient involvement and patient satisfaction, while it does not mediate the relationship between image and patient satisfaction. This study contributes to understanding patient behavior by using a framework of patient trust and satisfaction in medical eye clinics, which can also be applied to other public companies.